Clinical significance of the combined systemic immune-inflammatory index and prognostic nutritional index in predicting the prognosis of patients with extensive-stage small-cell lung cancer receiving immune-combination chemotherapy - Bingbing Wang; Jingdan Zhang; Yingnan Shi; Yan Wang (BMC Cancer)
Abstract Background The therapeutic efficacy and prognosis of various tumors can be assessed using the systemic immune-inflammatory index (SII) and prognostic nutritional index (PNI). Despite their potential, no studies have investigated the prognostic value of the combined SII-PNI score for outcomes in patients with extensive small cell lung cancer (ES-SCLC) treated with chemotherapy and immune checkpoint inhibitors (ICIs). Materials and methods Our study retrospectively examined 213 ES-SCLC patients treated with chemotherapy and ICIs across two institutions. The patients were divided into three groups based on their SII-PNI scores. Cox regression analysis was employed to identify independent prognostic factors. A nomogram was constructed based on these independent factors. With 1000 repeated samples, the bootstrap method was used to validate the nomogram model internally. The model’s performance was assessed using calibration curves, receiver operating characteristic (ROC) curves, and decision curve analysis (DCA). Result Before and after chemotherapy with immune checkpoint inhibitors (ICIs), SII was significantly higher in the PD group compared with the PR group (both p < 0.05). In the meantime, PNI was considerably lower in the PD group than in the PR group (both p < 0.01). Kaplan-Meier curves demonstrated that patients with a low SII-PNI had prolonged progression-free survival (PFS) and overall survival (OS) compared to those with a high SII-PNI (all p < 0.01). Multivariate Cox analysis showed that PS = 1, bone metastasis, brain metastasis, and SII-PNI = 1,2 after four treatment cycles were independent risk factors for shorter OS and were included in the nomogram model. The ROC curves, C-index, and DCA curves confirm that the SII-PNI scores-based nomograms have strong predictive accuracy for OS. Conclusion There was a significant correlation between pre- and post-treatment SII-PNI and treatment effect in ES-SCLC. The SII-PNI score after four treatment cycles is a useful prognostic indicator for ES-SCLC patients receiving chemotherapy combined with immune checkpoint inhibitors (ICIs).